The Suitability of INR (International Normalized Ratio) of Atrial Fibrillation Patients with Warfarin Therapy in Hospital â€œXâ€ Jakarta January - December 2024 - Aisyah, Vivi Nur; Futihat, Chilyati Eky; Arianti, Anisa Rachmita (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
Atrial fibrillation is a supraventricular arrhythmia with irregular atrial activation. One of the therapies that can be given is vitamin K antagonist class anticoagulants, namely warfarin. Bleeding often occurs in patients receiving warfarin therapy, so the use of anticoagulants must be balanced with an examination of the International Normalized Ratio. This study aims to evaluate the relationship between warfarin dose and the International Normalized Ratio value of atrial fibrillation patients at â€œXâ€ hospital in Jakarta. The method used was a non-experimental analytic, cross-sectional design using medical record data. Data were processed using SPSS version 25 with the Spearman Rank method. The inclusion criteria used in this study were outpatients with a diagnosis of atrial fibrillation, aged 25 to â‰¥ 85 years, receiving warfarin therapy, and having complete laboratory examination results, including International Normalized Ratio values. The number of samples that met the inclusion criteria was 60 patients. The results showed that patients with warfarin therapy were more male patients, namely 31 patients (52%), the most age range was 55-64 years (38%), most International Normalized Ratio examinations were carried out 1-4 times a year (73%), and patients with an International Normalized Ratio value of 2-3 were 13 people (21%). Statistical tests showed no significant relationship between warfarin dose and International Normalized Ratio value, the p value obtained was 0.164, which means that there is no significant relationship between the difference in the use of warfarin doses in atrial fibrillation patients at â€œXâ€ Hospital Jakarta, January - December 2024, to the suitability of INR values.